AB0509 SUSPENSIVE EFFICACY OF TOCILIZUMAB IN TREATMENT-NAÏVE PATIENTS WITH TAKAYASU ARTERITIS: TOCITAKA FRENCH PROSPECTIVE MULTICENTER OPEN-LABELLED TRIAL. (13th June 2020) - Mekinian, A.; Saadoun, D.; Jerome.Connault@chu-Nantes.Fr, J. C. N. F.; I-Quere@chu-Montpellier.Fr, I. Q. M. F.; Jégo, P.; Nicolas.Limal@aphp.Fr, N. L. F.; Wxv, W.; Gottenberg, J. E.; Vautier, M.; Lea.Savey@aphp.Fr, L. S. F.; Cacoub, P.; Fain, O.
Abstract : Objectives: To assess long term efficacy of tocilizumab in treatment-naive patients with Takayasu arteritis (TAK). Methods: In this multicenter, prospective, open-labelled trial, we aim to evaluate the benefit of adding tocilizumab to steroids in treatment-naïve patients with TAK, on discontinuation of steroids after 6 months of tocilizumab treatment, and to assess relapse-free survival following tocilizumab discontinuation. Results: Thirteen patients with TAK were included, with a median age of 32 years [19-45] and 12 (92%) females. Six (54%) patients met the primary end-point. Among 11 (85%) patients which achieved remission at 6 months, 6 (54%) have reached primary endpoint.. Among the 5 remaining patients which continued steroids, 3 had a prednisone-equivalent dosage < 5mg/day. A significant decrease of disease activity was observed after 6 months of tocilizumab therapy: decrease of median NIH scale (3 [3-4] at baseline, versus 1 [0-2] after 6 months; p <0.001), ITAS-2010 score (5 [2-7] versus 3 [0-8]; p = 0.002), and ITAS-A score (7 [4-10] versus 4 [1-15]; p = 0.0001)]. All patients discontinued tocilizumab after 7 infusions, and no other immunosuppressive drugs was introduced, except for 1 patient which received methotrexate. After 9 and 12 months, respectively 7 (54%) and 6 (50%) patients achieved remission with less than 7.5 mg/day of prednisone, and 9 (69%) and 9 (75%) with doses <10 mg/day. During the 12 months follow-up after tocilizumab discontinuation, a relapse occurred among 5 patients (45%) out of 11 in which achieved remission after 6 months of tocilizumab. No severe AEs were considered related to study treatment and none required tocilizumab interruption or dose reduction. No deaths have occurred during the study period. Conclusion: Tocilizumab seems an effective steroid sparing therapy in TAK but its effect appears to be suspensive. Disclosure of Interests: Arsene Mekinian: None declared, david Saadoun: None declared, jerome.connault@chu-nantes.fr jerome.connault@chu-nantes.fr: None declared, i-quere@chu-montpellier.fr i-quere@chu-montpellier.fr: None declared, Patrick Jégo: None declared, nicolas.limal@aphp.fr nicolas.limal@aphp.fr: None declared, wxv wxv: None declared, Jacques-Eric Gottenberg Grant/research support from: BMS, Pfizer, Consultant of: BMS, Sanofi-Genzyme, UCB, Speakers bureau: Abbvie, Eli Lilly and Co., Roche, Sanofi-Genzyme, UCB, Mathieu Vautier: None declared, lea.savey@aphp.fr>; lea.savey@aphp.fr>;: None declared, Patrice cacoub: None declared, olivier fain: None declared